SR Titans Conquer Skytrex Sg Congkak / Muhamad Afiq Ahmad and Muhammad Amir Iman Abdil Mutaib - Ahmad, Muhamad Afiq; Abdil Mutaib, Muhammad Amir Iman (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Hulu Langat: On 3rd May 2023, SR Titans organized an exciting field trip that combined adventure and nature, as well as marketing education. The outdoor excursion proved to be a memorable and educational experience for the enthusiastic students. Accompanied by their lecturer, Mr. Razif Bin Sazali, the students embarked on a journey to a picturesque outdoor recreation area renowned for its scenic beauty and sporting activities. The objective of the field trip was to highlight the intersection of outdoor recreation and sports marketing while emphasizing the importance of promoting these activities to a broader audience. The Academic Visitation Program serves as an activity that supports the practical teaching and learning process of students and allows them to apply the leisure resource management activities learned in this semester’s courses. This promotes team spirit and collaboration while meeting the requirements of Targeted Recreational Resource Management (SMG602). The students of SR Titans went to Skytrex Adventure Sg Congkak, an exciting outdoor adventure park located in Hulu Langat, Malaysia. This visit was an important one since it helped expose the students to the industry and allowed them to gain insights and interact with professionals in their field.